1980
DOI: 10.1152/jappl.1980.49.4.676
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to static exercise in distance runners and weight lifters

Abstract: Sixty individuals including 17 competitive weight lifters (CWL), 12 competitive long-distance runners (LDR), 7 amateur (noncompetitive) weight lifters (AWL), 14 heavy controls (HC), and 10 light controls (LC) were studied at supine rest and during static exercise at 40% of maximal voluntary contraction. Blood pressures were similar in all groups at rest (R) and exercise (EX), but the heart rate (HR) and calculated double product (DP) of the LDR were lower at rest (HR: 53 +/- 2.9 beats/min, DP: 6,346 +/- 402) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 24 publications
3
9
1
1
Order By: Relevance
“…The contrast between these studies and ours is that our tests were performed at a higher exercise intensity and with a greater amount of active muscle mass. Probably this produced two main differences: in this study the weight lifters showed a greater decrease in end-diastolic volume than previously re ported [7,12], reflecting diminished venous return following elevated intrathoracic pres sure on lifting weight. This may be attribut able to years of intensive weight lifting and may explain the unique pattern of response of left ventricular diastolic volumes referred to above.…”
Section: Responses To Isometric Contractioncontrasting
confidence: 49%
“…The contrast between these studies and ours is that our tests were performed at a higher exercise intensity and with a greater amount of active muscle mass. Probably this produced two main differences: in this study the weight lifters showed a greater decrease in end-diastolic volume than previously re ported [7,12], reflecting diminished venous return following elevated intrathoracic pres sure on lifting weight. This may be attribut able to years of intensive weight lifting and may explain the unique pattern of response of left ventricular diastolic volumes referred to above.…”
Section: Responses To Isometric Contractioncontrasting
confidence: 49%
“…However, these cardiac muscle adaptations appear to have little effect on systolic (21,23,28) and diastolic function (7,8). Much like hemodynamic changes during resistance training stimulate adaptations to cardiac muscle, alterations in the work of breathing due to resistance training could lead to adaptations in respiratory muscle function that improve exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate, for example, shows a rightward shift in its relationship with running speed as a consequence of chronic endurance training, although values corresponding to physiological markers such as LT and VT2 remain stable . This could be related to an increase in cardiac volume due to endurance training , leading to an increase in stroke volume and allowing a reduced heart rate for the same cardiac output. Breathing pattern is another factor that influences cycling performance, because professional cyclists have been reported to lack a tachypnoeic shift at high workloads, possibly indicating a more efficient use of their respiratory muscles .…”
Section: What Is Endurance Performance?mentioning
confidence: 99%